Association of sex with the global burden of vision impairment caused by neonatal preterm birth: An analysis from the global burden of disease study 2019 - Ye, Xin; Wang, Jun; Zhong, Xiaxing; Qiu, Wangli; Yang, Shangchao; He, Shucheng; Lou, Lixia; Shen, Lijun (Frontiers in Public Health, 2022)
Aims: To investigate the sex-specific global burden of neonatal preterm birth (NPB) vision impairment by year, age, and socioeconomic status using years lived with disability (YLDs). Methods: The global, regional, and national sex-specific YLD numbers, crude YLD rates, and age-standardized YLD rates of NPB-related moderate and severe vision loss and blindness were obtained from the Global Burden of Disease Study 2019. The Wilcoxon test and linear regression were used to investigate the relationship between sex difference in age-standardized YLD rates and the Human Development Index (HDI). Results: Between 1990 and 2019, the gender disparity in age-standardized YLD rates for NPB-related vision impairment remained stable, increasing from 10.2 to 10.4 for men and 10.3 to 10.7 for women, with women consistently having higher age-standardized YLD rates. Between the ages of 25 and 75, women had higher YLD rates than males, with the biggest disparity in the 60-64 age group. In 2019, sex difference in age-standardized YLD rates across 195 nations was statistically significant. Women had higher age-standardized YLD rates than men in both low (Z = -3.53, p < 0.001) and very high HDI countries (Z = -4.75, p < 0.001). Additionally, age-standardized YLD rates were found to be adversely associated with HDI (male: Standardized β = -0.435, female: Standardized β = -0.440; p < 0.001). Conclusion: Despite advancements in worldwide NPB health care, sexual differences in NPB-related vision impairment burden showed little change. Female had higher burden than male, particularly in low and very high socioeconomic status countries.